Teaching Techniques Used By Teacher To Develop Students' Vocabulary At The Second Grade Of Smp N 1 Nguter Sukoharjo In 2016/2017 Academic Year - Lestari, Leni, Mauly Halwat Hikmat, Ph. D (2017)
This research aims at describing the technique used by the teacher to develop students' vocabulary, the purposes of each technique, and the problem faced by the teacher. The study is descriptive qualitative research. The data in this study were: the techniques used by teacher to develop students' vocabulary, fields note and interview script. The data are taken from observation, interview, and document. The technique for analyzing data is data reduction, data display, and conclusion and verification. The finding of the research shows that there are some techniques used by the English teacher such as: memorization, synonym, antonym, translation, and self-defining context. The purposes of each technique are (1) memorization can improve the students' pronunciation and help the students to develop their memorization, (2) synonym can help the students to understand the word which has similar meaning, (3) antonym is to help the students to understand a pair of opposites meaning of words and may it can enrich students' vocabulary, (4) translation can help the students familiar with the word and the students understand the meaning of the words or sentences that they have not understood before. (5) self-defining context can interest the students to observe all of things in environment and it can help the students to define things based on the context. The problems faced in developing students' vocabulary are classroom management, the students' learning motivation, and vocabulary accomplishment problems.